Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1097/nmd.0000000000001351
|View full text |Cite
|
Sign up to set email alerts
|

Identifying, Assessing, and Treating Korsakoff Syndrome Patients

Abstract: Objectives consist of updating published reports on the recognition, assessment, and care of patients with Wernicke-Korsakoff syndrome (WKS). Methods included defining relevant terms, describing core clinical phenomena, conducting meaningful reviews for latter-day WKS publications, and selecting instructive case examples. Findings covered epidemiology, precipitants, neuroimaging studies, alternate learning strategies in WKS, adjunctive treatments, and promising research. In conclusion, patients, their family m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 82 publications
(101 reference statements)
0
2
0
2
Order By: Relevance
“…It has been reported that neurons could be irreversibly damaged by a lack of thiamine, thus failing to respond to thiamine treatment even when presented with adequate amounts [ 9 , 17 ]. Bolus IV thiamine infusion is mostly considered unhelpful after patients have passed the acute stage of Wernicke syndrome [ 6 , 12 ]. This could explain Mr. A's failure to improve following his IV thiamine infusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that neurons could be irreversibly damaged by a lack of thiamine, thus failing to respond to thiamine treatment even when presented with adequate amounts [ 9 , 17 ]. Bolus IV thiamine infusion is mostly considered unhelpful after patients have passed the acute stage of Wernicke syndrome [ 6 , 12 ]. This could explain Mr. A's failure to improve following his IV thiamine infusion.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, alcohol use can also lead to Wernicke's encephalopathy and Korsakoff syndrome. The clinical presentation of each of these two conditions can be diverse and complicated [ 6 9 ]. Moreover, patients with severe mental illnesses such as schizophrenia and bipolar disorder can also gradually develop cognitive deficits [ 4 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Det anslås at fra 50 til 70-80 % av AUD-pasienter har en eller annen grad av kognitiv forstyrrelse, og at en andel av disse igjen har en kognitiv svekkelse av klinisk betydning (Bates et al, 2013;Bernardin et al, 2014;Nixon & Lewis, 2019). En liten andel personer med høyt alkoholinntak over lang tid vil kunne utvikle mer alvorlige kognitive svekkelser, som Korsakoffs syndrom eller alkoholassosiert demens (Westermeyer et al, 2021).…”
Section: Kognitive Vanskerunclassified
“…Det anslås at fra 50 til 70-80 % av AUD-pasienter har en eller annen grad av kognitiv forstyrrelse, og at en andel av disse igjen har en kognitiv svekkelse av klinisk betydning (Bates et al, 2013;Bernardin et al, 2014;Nixon & Lewis, 2019). En liten andel personer med høyt alkoholinntak over lang tid vil kunne utvikle mer alvorlige kognitive svekkelser, som Korsakoffs syndrom eller alkoholassosiert demens (Westermeyer et al, 2021).…”
Section: Kognitive Vanskerunclassified